A two step synthesis of a key unit B precursor of cryptophycins by asymmetric hydrogenation - Sammet, Benedikt; Brax, Mathilde; Sewald, Norbert (Beilstein journal of organic chemistry, 2011)
A novel highly enantioselective two step access to a unit B precursor of cryptophycins in good yields from commercially available starting materials has been developed. The key step is an asymmetric hydrogenation using the commercially available [(COD)Rh-( R , R )-Et-DuPhos]BF 4 catalyst. The synthetic route provides the advantage of less synthetic steps, proceeds with high yields and enantioselectivity, and avoids hazardous reaction conditions.